Early Detection and Treatment of Pediatric Amblyopia: A Cost-Benefit Analysis in the Indonesia: A Literature Review - Tedjaprasadja, Leonardo (Journal of Diverse Medical Research: Medicosphere, 2025)
Background: Amblyopia is a leading cause of preventable visual impairment in children. Despite effective treatment, delayed diagnosis limits visual recovery and may reduce lifetime productivity. In Indonesia, where pediatric vision screening is not yet universal, undiagnosed amblyopia may lead to lifelong productivity losses. This study evaluates the cost-effectiveness of early screening and intervention for amblyopia from a societal perspective. Methods: A Markov model simulated a cohort of 100,000 children aged 3 over a 70-year period. Two strategies were compared: (1) early vision screening and treatment through primary care (e.g., Puskesmas), and (2) no structured screening. Costs, utilities, productivity losses, benefit-cost ratio were estimated using local data where available and adjusted using purchasing power parity (PPP) and Indonesian-specific parameters from WHO-CHOICE, BPJS Kesehatan reimbursement rates, and labor market data. Results: The findings affirm that nationwide early screening and treatment for amblyopia in Indonesia are not only clinically effective but also economically justified. The estimated lifetime productivity gain per successfully treated child was USD 4,130, yielding a total indirect savings of over USD 11.3 million. The benefit-cost ratio was 7.8:1, The calculated ICER was USD 183.54 per QALY gained Conclusion: Universal amblyopia screening in Indonesia is cost benefit and highly cost-effective. Integration into school-based health programs and the Puskesmas system could optimize early detection, reduce visual disability burden, and improve long-term national productivity.